2004
DOI: 10.1128/aem.70.3.1393-1396.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR, Electrochemical Enzyme-Linked Immunosorbent Assays, and the Standard Culture Method for Detecting Salmonella in Meat Products

Abstract: An electrochemical enzyme-linked immunosorbent assay (ELISA) coupled with flow injection analysis (ELISA-FIA) and a PCR-based method using ST11 and ST15 primers for detecting salmonellae in meat were evaluated in comparison with the International Organization for Standardization (ISO) culture method. The methods were applied to experimentally contaminated and naturally contaminated meat samples. The results showed that both ELISA-FIA and PCR allowed detection of salmonella in a product contaminated with a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 24 publications
(26 reference statements)
1
33
0
Order By: Relevance
“…In this area, we recently (Croci et al 2001) reported the development of an electrochemical ELISA for the detection of Salmonella in meat samples using a sandwich format and a conventional ELISA plate; after all immunological and enzymatic reactions are in place, the mixture contained in each well is injected into a flow injection analysis (FIA) system coupled to an electrochemical cell. Although the effectiveness of this system has been demonstrated (Croci et al 2001(Croci et al , 2004 for the analysis of meat samples, a certain level of skill and quite complex instrumentation are required.…”
Section: Introductionmentioning
confidence: 99%
“…In this area, we recently (Croci et al 2001) reported the development of an electrochemical ELISA for the detection of Salmonella in meat samples using a sandwich format and a conventional ELISA plate; after all immunological and enzymatic reactions are in place, the mixture contained in each well is injected into a flow injection analysis (FIA) system coupled to an electrochemical cell. Although the effectiveness of this system has been demonstrated (Croci et al 2001(Croci et al , 2004 for the analysis of meat samples, a certain level of skill and quite complex instrumentation are required.…”
Section: Introductionmentioning
confidence: 99%
“…confirmation of biochemically identified isolates was done by PCR using ST11 and ST15 primers (F: 5'-AGCCAACCATTGCTA AATTGCCGCA-3'; and R: 5'-GGTAGA AATTCCCAGCGG GTACTGG-3'), which amplify a fragment of 429 bp that is specific for Salmonella spp. [13].…”
Section: Molecular Characterization Of the Isolatesmentioning
confidence: 99%
“…An enzyme-linked immunosorbent assay coupled with flow injection analysis (ELISA-FIA) was developed and compared with the ISO culture method for detecting salmonellae in meat samples (Croci, Delibato, Volpe, De Medici, & Palleschi, 2004). It was found that the ELISA-FIA had a detection limit of 1-10 salmonellae per 25 g food when a 5-h pre-enrichment step was employed.…”
Section: Detection Of Salmonella In Food Samples By Immunoassay-basedmentioning
confidence: 99%